Reptiles - Indraneil, Das; Min, Pui Yong; Adi Shabrani, Mohammad Ridzuan; Veronica, Leah; Awang Ikhwan, Khairul (UNIMAS Publisher and Natural History Publications (Borneo) Sdn Bhd, 2024)
The chapter provides an inventory of the reptile fauna of the Baleh region